Ammonia induces changes in carbamoyl phosphate synthetase I and its regulation of glutamine synthesis and urea cycle in yellow catfish Pelteobagrus fulvidraco. Issue 120 (January 2022) - Zhang, Muzi; Wang, Shidong; Sun, Liying; Gan, Lei; Lin, Yanhong; Shao, Jian; Jiang, Haibo; Li, Ming
Abstract: Fishes can adapt to certain levels of environmental ammonia in water, but the strategies utilized to defend against ammonia toxicity are not exactly the same. The carbamyl phosphate synthase I (CPS I) plays an important role in the regulation of glutamine synthesis and urea cycle, which are the most common strategies for ammonia detoxification. In this study, CPS I was cloned from the yellow catfish. The full-length cDNAs of the CPS I was 5 034 bp, with open reading frames of 4 461 bp. Primary amino acid sequence alignment of CPS I revealed conserved similarity between the functional domains of the yellow catfish CPS I protein with CPS I proteins of other animals. The mRNA expression of CPS I was significantly up-regulated in liver and kidney tissues after acute ammonia stress. The CPS I RNA interference (RNAi) down-regulated the mRNA expressions of CPS I and ornithine transcarbamylase (OTC), but up-regulated glutamine synthetase (GS) and glutamate dehydrogenase (GDH) expressions in primary culture of liver cell after acute ammonia stress. Similarly, the activity of enzymes related to urea cycle decreased significantly, while the activity of enzymes related to glutamine synthesis increased significantly. The results of RNAi in vitro suggested that when the urea cycle is disturbed, the glutamine synthesis will be activated to cope with ammonia toxicity. Highlights: The full-length cDNAs of the CPS I was 5 034 bp. The CPS I expression was up-regulated under acute ammonia stress. When urea cycle is disturbed, the glutamine synthesis will be activated.